Internalizing Islamic moderation: a model approach for educational institutions - Kuswanto, Edi; Mubin, Muhammad Nurul; Suharsono; Kurniawan, Dwi Setia (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2023)
This paper examines the methods of internalizing the value of moderation in Islamic education, specifically within the context of at-tawāsuṭ wal i’tidāl (moderation and justice) in schools, drawing on Thomas Lickona’s character education theory. The research methodology employed in this study includes a literature review and a survey. Although the survey presents some numerical data, the overall study is qualitative. The findings show that the core value of moderation in the Nahdlatul Ulama is at-tawāsuṭ wal i’tidāl, which will spell out various values of moderation derivatives. The processes of internalizing such Islamic moderation in schools – in the perspective of Lickona- were done along three stages: 1) Knowing, conducted through TCL (Teacher-Centered Learning) strategy by applying CTL (Contextual Teaching and Learning) approach and group discussion method; 2) Feeling, achieved through strengthening intra classroom activities, editing, and habituating; and 3) Doing, which is more implemented in intra and extracurricular activities. This research offers insights into internalizing Islamic moderation in schools, drawing on the perspective of at-tawāsut wal i’tidal and Lickona’s character education theory. It contributes to the formulation of a model approach that can be implemented by various educational institutions, particularly schools, to foster Islamic moderation among students.